Republic of Latvia : Fifth Review Under the Stand-By Arrangement and Financing Assurances Review, Request for Waiver of Nonobservance of a Performance Criterion, and Proposal for Post-program Monitoring. (IMF Staff Country Reports; Country Report ;, 2012)
Latvia's economy continues to recover, but the worsening global outlook is likely to hurt growth. Implementation of the program has made the economy more robust to shocks, but risks remain that could derail the recovery and the goal of euro adoption. Spillovers from the euro area crisis could increase-reducing growth and increasing capital outflows-and complicate plans to tap international capital markets. The authorities' macroeconomic strategy has centered on substantial wage and price cuts and productivity growth to improve competitiveness and reduce external imbalances.